ИЛИМИЙ ИЗЕРТЛЕЎДИҢ ТЕОРИЯЛЫҚ МЕТОДОЛОГИЯЛЫҚ МАШҚАЛАСЫН ИСЛЕП ШЫҒЫЎДА АБУ РАЙХАН БЕРУНИЙДИҢ ҚОСҚАН ҮЛЕСИ - Есназарова, З.Б.; Тлеумуратова, З.М.; Утемисов, А.А. (FAN va JAMIYAT, 2024)
This article analyzes and examines the significant contribution of the Central Asian encyclopedist Abu Rayhan al-Beruni to the development of theoretical and methodological issues in scientific research, evaluating his scholarly approach by both domestic and international scholars.